PARTISIPASI MASYARAKAT DALAM PENGELOLAAN OBJEK DAN DAYA TARIK WISATA KORIDOR JALUR LINTAS SELATAN KABUPATEN MALANG - Ramanda, Pramadika; Hakim, Luchman; Pangestuti, Edriana (FIA UB, 2020)
Local community participation in tourism development has been identified crucial, but it was few discussed in South Malang Regency, East Java. The purpose of this study is to examine the role of the community in the development of natural tourism attraction along Southern corridors on East East Java from Balekambang to Sendang Biru. Field survey and interviews were implemented to generate infromation related to the types of local community participation in tourism along the corridor. This research shows that there are two important bodies in natural resources management that influeces the management of recreation sites mnagament, namely Office of Tourism of Malanag Regency and Perhutani KPH Malang. The form of community participation in the JLS Beach Tourism Corridor in South Malang tends to be dominated by the functional participation model. This participation model forms a community to jointly develop, give advice and plan tourist destinations as a form of appreciation for the existence of local community institutions but the decision makers in planning tourist destinations are dominated by parties outside the community, namely Perhutani.